Differential calculus aptitude: A correlation to self-efficacy and self-regulation of pre-service mathematics teachers - Garcia, Von Xernan M.; Ibarra, Florante P.; Antalan, John Rafael M.; Taganap, Eduard C. (Edelweiss Applied Science and Technology, 2025)
This study explores the relationship between the two independent variables, self-efficacy (SE) and self-regulation (SR), and the dependent variable, mathematics aptitude in differential calculus, of pre-service mathematics teachers from Central Luzon State University (CLSU). The study also investigates which parameters of SE and SR are the best predictors of mathematics aptitude in differential calculus. The study utilizes a descriptive correlational research design with stratified random sampling, and the respondents are 71 pre-service mathematics teachers. The data collection methods used include a 24-item self-efficacy scale, a 31-item self-regulation scale, and a 30-item researcher-made questionnaire on differential calculus. Results revealed that the relationship between self-efficacy and mathematics aptitude has a significant positive correlation, as does the relationship between self-regulation and mathematics aptitude in differential calculus. Stepwise regression analysis discovered that vicarious experiences (SE), social persuasion (SE), and external regulation (SR) are the best predictors of mathematics aptitude in differential calculus. This study highlights the significance of enhancing mathematics performance by improving the self-efficacy and self-regulation of the students. Understanding these variables will greatly assist in designing effective teaching strategies to improve students’ mathematical abilities and performance.